STRATEGIES FOR DEVELOPING ACADEMIC AND SCIENTIFIC PARTNERSHIP BETWEEN UNIVERSITIES OF UKRAINE AND CHINA (Comparative Professional Pedagogy, 2024)
The article defines the concept of academic and scientific partnership in higher education and shows that universities are the centers of its development in the context of internationalization and globalization of education. The main forms of academic and scientific partnership between universities of Ukraine and China are identified. It is found that Confucius Institutes play an important role in its promotion. It is substantiated that an open and competitive system of international scientific cooperation and academic exchange programs between Ukraine and China provides domestic universities with the opportunity to fully utilize the scientific and educational resources of their own country as well as of the partner country; organize joint research activities of domestic and foreign scientific and pedagogical personnel; develop a national strategy for the scientific cooperation in education. Aspects of modern scientific and educational research that necessitate its implementation within the framework of international partnerships are identified. The importance of the “One Belt, One Road” initiative for international partnership in education aimed at implementing innovative educational resources and its expansion through joint research, scientific consulting, educational forums, accepting delegations, organizing internships, academic exchange programs, participation in conferences, creating joint projects, research and educational centers, etc. is emphasized. Ukrainian universities with the best achievements in establishing academic and scientific partnerships with China are identified.Strategies for developing academic and scientific partnership between universities of Ukraine and China are outlined. They presuppose expanding the potential and opportunities for cooperation; using the services of intermediary organizations; using network information technologies to create an effective platform for the internationalization of universities; attracting educational partners from abroad, conducting joint training; preraring teaching and management staff of domestic universities to implement internationalization programs; strengthening the competitiveness of educational programs and services of domestic higher education institutions in the international arena; strengthening cultural relations between the countries and developing their national identity; forming a new image of the Chinese in the Ukrainian educational space; constantly updating the content of international exchange programs; sharing educational resources.
Keywords: academic and scientific partnership; international cooperation; universities; China; academic exchange programs; scientific research; internships; internationalization of education